PENGARUH PENERAPAN PENDIDIKAN SEKS (MEDIA ULAR TANGGA) TERHADAP KEMAMPUAN PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK JALANAN DI KAMPUNG SAVANA KOTA MAKASSAR - Nurbaya, Sitti; Simon, Merlis (Journal of Islamic Nursing, 2019)
The Indonesian Child Protection Commission confirmed the sexual violence against children was still a major problem. In 2015 the category of children dealing with the law ranked first, namely cases of sexual violence against children (Rape, molestation, sodomy / pedophilia) as many as 18% or 193 victims of the second place violence as victims of physical violence as much as 17% or 182 cases and the third order as children perpetrators of sexual violence 12.9% or 138 cases. The Makassar City Women's Empowerment and Child Protection Agency noted that there were at least 1,160 cases of child abuse in Makassar City in 2017. This was due to the lack of efforts of children, adolescents, parents and teachers to prevent early. The purpose of this study was to determine the effect of the implementation of sex education (ladder snake media) on the ability to prevent sexual violence on street children in Savana, Makassar City. The type of this research used a Quasy Experimental research design with a Pre-post test design approach. This research was conducted in Savana Village Bangkala Village, Manggala. District, Makassar on March 27-30 August 2019. The population of  the study was 45 children, based on the population, then taken a sample of 40 respondents. Statistical test results showed there was an influence of sex education (snake ladder media) on the prevention of sexual violence in children with a value (p = 0,000, smaller than ɑ = 0.05). So, it can be concluded that there was an influence on the application of sex education (snake ladder media) to prevention of sexual violence against street children in Savana village, Makassar City.Keywords: Sex Education, Snakes and Ladders, Sexual Violence, Street Children